NutriPlay: Bilingual Mobile App for Nutrition and Cultural Food Education (JPK : Jurnal Proteksi Kesehatan, 2026)
Digital nutrition education interventions have shown promise, yet most remain monolingual and rarely integrate local cultural food content, limiting their relevance in multilingual, culturally diverse settings such as Indonesia. This study addresses this gap by evaluating NutriPlay, a bilingual (Indonesian-English) mobile application that uniquely integrates nutrition education, English vocabulary acquisition, and Indonesian cultural food awareness—a combination not previously examined among elementary school students. A quasi-experimental one-group pre-post intervention study involved 30 fifth-grade students in Pekanbaru, Riau. Overall nutrition knowledge improved significantly from 37.2% to 83.1% (mean gain +45.9%, t(29)=18.47, p
Keywords: Nutrition Education; Mobile Health; Bilingual Application; Cultural Awareness; Elementary School